Watson to Handcock Copy Notice, 1839.
'Sir,
In reply to your Notice of the 3rd day of April last stating that you had purchased from the Ecclesiastical Commissioners the fee and inheritance of that part of the farm of St Sepulchres held by you under a lease from the Archbishop of Dublin the Conveyance of which you State bears date 22nd day of March last and also requiring me as your tenant to a part of the said Farm under and by virtue of a certain Lease for 21 years in which is contained a toties Quoties clause of renewal ... Dated the 30th day of August 1839 William Watson. Served a copy of the above notice on Mr Handcock Senior on Saturday morning the 31stday of August 1839 Alex[ander] MacMillan.'
External signed 'Thomas Jameson' and [faded].